Bedside haemodynamic monitoring: experience in a general hospital. Issue 6386 (16th July 1983) - Bayliss, J; Norell, M; Ryan, A; Thurston, M; Sutton, G C
Abstract : Bedside right heart haemodynamic monitoring was carried out on 55 occasions over 18 months in the cardiac care unit of a district general hospital. The technique was used to assist in the management of 27 patients with acute heart failure by helping to select appropriate treatment. Although the catheters were flow guided, insertion and positioning were facilitated by fluoroscopy. The procedure was safe, with one complication arising; technical difficulties occurred in eight cases. Prediction of cardiac output and left ventricular filling pressure by clinical assessment proved to be accurate in only 55% of cases: in patients with acute heart failure there was a tendency to underestimate the cardiac output (25%) and overestimate the left ventricular filling pressure (37%), whereas in patients with chronic heart failure the filling pressure was more accurately estimated (71%). Haemodynamic measurement was often invaluable in selecting and adjusting treatment, particularly in critically ill patients.